37. SUCCESSFUL EMERGENCY MANAGEMENT OF HEMORRHAGIC SHOCK DUE TO CAROTID ARTERY ANEURYSM - THE ROLE OF AWAKE INTUBATION INDIFFICULT AIRWAY CONTROL (Vietnam Journal of Community Medicine, 2024)
Background: A Case of Life-Threatening Bleeding Caused by Rupture of an Internal Carotid Artery Aneurysm - The Role of Awake Tracheal Intubation in Emergency Difficult Airway ManagementObjective: To describe the clinical scenario, analyze the decision-making process in airway management, and apply the Difficult Airway Society guidelines for awake tracheal intubation (ATI) in adults.Methods: This case report details a clinical incident involving life-threatening bleeding from an internal carotid artery aneurysm caused by a fistula following radiotherapy for tongue cancer at Hong Ngoc Phuc Truong Minh General Hospital on March, 2024.Results: A 53-year-old male, diagnosed with tongue cancer two years prior, underwent surgery, radiotherapy, and chemotherapy. Days before admission, he experienced pain and bleeding from the right lateral neck due to an internal carotid artery aneurysm. An attempt at tracheal intubation for endovascular intervention at another hospital failed. Upon arrival at our emergency department, he exhibited massive neck hemorrhage, remained conscious, pale, with ongoing bleeding from a right neck fistula, and limited cervical motion due to irritation. He was breathing spontaneously without dyspnea, with pulse: 125 bpm; blood pressure: 98/53 mmHg; respiratory rate: 28 breaths/min; SPO2 93% (with a 10 l/min oxygen mask). A treatment strategy for permanent occlusion of the right internal carotid artery aneurysm was devised. Intubation was necessary for both endovascular intervention and resuscitation, predicting difficult mask ventilation, intubation, and front-of-neck access.Awake tracheal intubation using a fiberoptic scope via the nasal route was performed. The patient received light sedation with Midazolam, and the airway was topicalized with 10% Lidocaine spray over the mouth, tongue, and oropharynx mucosa. Continuous monitoring of heart rate, ECG, and oxygen saturation showed no decrease in oxygen levels, and the patient maintained spontaneous breathing throughout. Intensive treatment with crystalloid fluids and blood transfusion, along with right internal carotid embolization with a spring coil, effectively prevented massive hemorrhage. The patient was successfully extubated after three days in the ICU and discharged 15 days post-surgery without any neurological deficits.Conclusion: A well-planned strategy for difficult airway management is essential when challenging facemask ventilation, supraglottic airway device placement, tracheal intubation, or front-of-neck airway insertion is anticipated. Awake tracheal intubation ATI is highly successful and low-risk, making it the gold standard in managing predicted difficult airways. The decision to perform ATI depends on the clinical context. Successful ATI requires conscious sedation, maintenance of a patient airway, and adequate spontaneous ventilation, but ATI should also be considered in urgent situations.
Keywords: Awake intubation; difficult airway management; fiberoptic scope; emergency airway management